2016
DOI: 10.4236/ajps.2016.713160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17<i>β</i>-Estradiol on Growth, Primary Metabolism, Phenylpropanoid-Flavonoid Pathways and Pathogen Resistance in <i>Arabidopsis thaliana</i>

Abstract: Mammalian sex hormones are spread in the environment from natural and anthropogenic sources. In the present study, the effect of estradiol on Arabidopsis thaliana growth primary metabolism, phenylpropanoid and flavonoid pathways and pathogen resistance were investigated. Treatments of Arabidopsis plants with 10 and 100 nM 17β-estradiol resulted in enhanced root growth and shoot biomass. In addition, treated plants had an increased rate of photosynthesis with a concomitant increase in carbohydrate and protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(50 reference statements)
4
7
0
Order By: Relevance
“…affected by a high treatment with estrogens. These findings are in agreement with previous results that have shown a reduction of chlorophyll content in A. thaliana at 2704 µg L -1 and stimulation of carotenoids in Wolffia arrhiza (Lemnaceae) (at 10 -6 M) in response to 17β-E2 exposure (Czerpak and Szamrej, 2003a;Upadhyay and Maier, 2016b). Similar findings of a decline in photosynthesis with synthetic estrogen (EE2) contamination were reported in green alga Chlamydomonas reinhardtii and Dunaliella salina at 1893 µg L -1 and 100 ng L -1 (Pocock and Falk, 2014;Belhaj et al, 2017).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 93%
See 3 more Smart Citations
“…affected by a high treatment with estrogens. These findings are in agreement with previous results that have shown a reduction of chlorophyll content in A. thaliana at 2704 µg L -1 and stimulation of carotenoids in Wolffia arrhiza (Lemnaceae) (at 10 -6 M) in response to 17β-E2 exposure (Czerpak and Szamrej, 2003a;Upadhyay and Maier, 2016b). Similar findings of a decline in photosynthesis with synthetic estrogen (EE2) contamination were reported in green alga Chlamydomonas reinhardtii and Dunaliella salina at 1893 µg L -1 and 100 ng L -1 (Pocock and Falk, 2014;Belhaj et al, 2017).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 93%
“…5.4). However interestingly, at the 0.1 µg L -1 treatment improve the root length, which is in agreement with results obtained with other plant species such as A. thaliana (Upadhyay and Maier, 2016b), and chickpea (Erdal and Dumlupinar, 2011b). However, at doses higher than 50 µg L -1 , there was an inhibitory effect on root morphology.…”
Section: Effects Of Estrogens On Root Morphologysupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, it has been reported that E2 can improve antioxidative enzyme activities and avoid H 2 O 2 generation to reduce oxidative stress injury from heavy metal induced [ 41 ]. Furthermore, E2 can also disturb the expression of phenylpropanoid-flavonoid pathway genes and decrease the accumulation of phenols, flavonoids, and anthocyanins of plant cells [ 42 ]. For microalgae, there are also several mechanisms to protect themselves from the toxicity of contaminants [ 43 ].…”
Section: Discussionmentioning
confidence: 99%